A retrospective analysis of maize performance under low nitrogen stress conditions in sub-Saharan Africa - Gokoma, Stanley; Kamutando, Casper N.; Siwela, Muthulisi; Derera, John (Frontiers in Agronomy, 2025)
IntroductionFertilizer use in sub-Saharan Africa (SSA) is the lowest in theworld and has stagnated. Consequently low nitrogen (N) stress is one of the principal constraints to maize yields in this region. Therefore improving nitrogen use efficiency of maize varieties will result in higher nitrogen recovery rates, leading to less leaching of nitrogen as well as loss through nitrification and ammonification. This study aimed to: 1) Investigate the relationship between grain yield under low N and optimal conditions; and 2) Establish the level of variability in low N tolerance among elite Eastern and Southern African (ESA) maize varieties. MethodsFifty-eight paired trials, each consisting of 40 to 65 maize hybrids, were conducted under low N and optimal (i.e.,high N) conditions in five countries, in Eastern and Southern Africa during 2013-2015.Results and discussionThe level of yield reduction as a result of low N stress ranged from 8% to 91% across the 58 paired trails. Grain yield of hybrids ranged from1.69Mg ha-1 to 3.44 Mg ha-1 in the early maturity group and 1.71 Mg ha-1 to 3.35 Mg ha-1 in the intermediate to late maturity group, with heritability ranging from 0.25 to 0.53 and 0.29 to 0.76, in the respective two maturity groups. Under the low N stress. Pre-commercial hybrids that were bred for low N tolerance performed better than the old commercial hybrids and open pollinated varieties (OPVs). These results suggest that if more effort is devoted to selecting maize under low N conditions, significant yield gains can be realized with profound impact on maize productivity in SSA.